Bridging Gaps in Education Internship at Educationary Technocart - Agarwal, Subham (ATLAS SkillTech University, 2025)
During my internship at Educationary Technocart, I had the opportunity to engage deeply with various aspects of the EdTech industry. As a co-founder, my role involved working on numerous strategic and operational fronts. My primary responsibilities included analyzing customer feedback, developing and refining educational solutions, and contributing to the company's growth strategy. Throughout the internship, I focused on understanding the dynamics of customer satisfaction and its impact on educational product development. I worked closely with the team to gather and analyze user feedback, which was instrumental in enhancing our offerings and ensuring they met the evolving needs of students and educators. In addition to this, I contributed to market research efforts that explored the broader landscape of the EdTech sector, particularly in India. This involved identifying key trends, challenges, and opportunities within the industry. My findings helped shape strategic recommendations aimed at improving our market positioning and expanding our reach. The internship also provided me with valuable insights into the intersection of technology and education, as well as the operational challenges faced by startups in this sector. I had the chance to develop my skills in project management, data analysis, and strategic planning, all of which have been crucial in my professional growth. Overall, the experience at Educationary Technocart was highly enriching and has significantly contributed to my understanding of the EdTech industry. It has equipped me with practical skills and knowledge that I will carry forward into my future endeavors.
Project Report on Bridging Gaps in Education Internship at Educationary Technocart (2023-2025) Under the Guidance of Prof. Omkar Pandharkame
Keywords: market research; educational product development; strategic and operational fronts; EdTech industry; practical skills